Linc-ROR Promotes Osteogenic Differentiation of Mesenchymal Stem Cells by Functioning as a Competing Endogenous RNA for miR-138 and miR-145 - Feng, Lu; Shi, Liu; Lu, Ying-fei; Wang, Bin; Tang, Tao; Fu, Wei-ming; He, Wei; Li, Gang; Zhang, Jin-fang (Molecular therapy. Nucleic acids, 2018)
Long noncoding RNAs (lncRNAs), which serve as important and powerful regulators of various biological activities, have gained widespread attention in recent years. Emerging evidence has shown that some lncRNAs play important regulatory roles in osteoblast differentiation of mesenchymal stem cells (MSCs), suggesting a potential therapeutic strategy for bone fracture. As a recently identified lncRNA, linc-ROR was reported to mediate the reprogramming ability of differentiated cells into induced pluripotent stem cells (iPSCs) and human embryonic stem cells (ESCs) self-renewal. However, other functions of linc-ROR remain elusive. In this study, linc-ROR was found to be upregulated during osteogenesis of human bone-marrow-derived MSCs. Ectopic expression of linc-ROR significantly accelerated, whereas knockdown of linc-ROR suppressed, osteoblast differentiation. Using bioinformatic prediction and luciferase reporter assays, we demonstrated that linc-ROR functioned as a microRNA (miRNA) sponge for miR-138 and miR-145, both of which were negative regulators of osteogenesis. Further investigations revealed that linc-ROR antagonized the functions of these two miRNAs and led to the de-repression of their shared target ZEB2, which eventually activated Wnt/β-catenin pathway and hence potentiated osteogenesis. Taken together, linc-ROR modulated osteoblast differentiation by acting as a competing endogenous RNA (ceRNA), which may shed light on the functional characterization of lncRNAs in coordinating osteogenesis.